HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN PEMENUHAN KEBUTUHAN NUTRISI PADA ANAK USIA TODDLER (1-3 TAHUN) - Wulandari, Ria; Siska, Siska; Putra, Golan (JURNAL KESEHATAN TERAPAN, 2021)
Background: The World Health Organization (WHO) states that the number of cases of breast infections that occur in women such as cancer, tumors, mastitis, fibrocustic disease continues to increase, where breast cancer sufferers reach 1.2 million people who are diagnosed, and 12% of them. they. is a breast infection in the form of mastitis in postpartum women, this is due to a lack of knowledge about breast care. Objective: To determine the effect of the role of health workers, sources of information and support from husbands on the compliance of postpartum mothers in breast care. Methods: This type of research is quantitative using a cross sectional study design with a sampling technique using accidental sampling obtained a sample of 42 respondents. Results: The results showed that there was a significant relationship between sources of information and adherence of postpartum mothers to breast care p. The value of 0.028 ≤ α = 0.05, for the role of health workers there is a significant relationship with postpartum breast care compliance. p. value = 0.000 ≤ α = 0.05 and there is a significant relationship between husband's support and adherence to postpartum mothers for breast care p. value = 0.035 ≤ α = 0.05. Suggestion: puskesmas officers or health promotion program holders provide counseling in health education.Key words : Breast Care